Relationship of Identity and Commitment Towards Faculty's Performance of Laguna State Polytechnic University Faculty, Philippines - Pinuela, Freddie S. (International Journal of Social Learning (IJSL), 2023)
The relevance of curriculum in supporting high levels of learning and the articulation and promotion of comprehensive development-relevant education was stressed in Sustainable Development Goal Four (SDG 4). The study used a quantitative research design employing a descriptive-correlational approach. Forty (40) faculty members of Laguna State Polytechnic University (LSPU) from the College of Industrial Technology  (CIT) participated in the study, where purposive sampling was used in choosing the respondents. JASP software was used in analyzing the data in the study. Based on the findings, The relationship between identity, commitment, and faculty teaching performance is highly valued at LSPU. Furthermore, there is no substantial association between teachers' professional identities and commitment to instructors' performance. Thus, teachers' performance should be prioritized because it impacts the school's long-term success. Future researchers may use a qualitative research design in a different setting.